Influence of the distance in a roundhouse kick's execution time and impact force in Taekwondo - Falcó, C.; Alvarez, O.; Castillo, I.; Estevan, I.; Martos, J.; Mugarra, F.; Iradi, A. (Journal of Biomechanics, 2009)
Taekwondo, originally a Korean martial art, is well known for its kicks. One of the most frequently used kicks in competition is Bandal Chagui or roundhouse kick. Excellence in Taekwondo relies on the ability to make contact with the opponent's trunk or face with enough force in as little time as possible, while at the same time avoiding being hit. Thus, the distance between contestants is an important variable to be taken into consideration. Thirty-one Taekwondo athletes in two different groups (expert and novice, according to experience in competition) took part in this study. The purpose of this study was to examine both impact force and execution time in a Bandal Chagui or roundhouse kick, and to explore the effect of execution distance in these two variables. A new model was developed in order to measure the force exerted by the body on a load. A force platform and a contact platform were used to measure these variables. The results showed that there are no significant differences in terms of impact force in relation to execution distance in expert competitors. Significant and positive correlations between body mass and impact force (p<.01) seem to mean that novice competitors use their body mass to generate high impact forces. Significant differences were found in competitive experience and execution time for the three different distances of kicking considered in the study. Standing at a certain further distance from the opponent should be an advantage for competitors who are used to kick from a further distance in their training.